Characteristics of Natural Fibers and Methods of Obtaining - Usmanova Shakhnoza Anvarovna; Axmadjonova Nozanin; Ochilov Tulkin Ashurovich; Raximova Umida Baxriddin qizi; Bolqiyev Sobirjon Kholnazarovich (Research Parks Publishing LLC, 2022)
The types of Sansevera plants were analyzed, and research was conducted on which type of fiber can be obtained from them. The results of the study showed that only one type of fiber can be obtained.